2003
DOI: 10.1007/s00204-003-0488-1
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive and inducible levels of CYP1A1 and CYP1A2 in rat cerebral cortex and cerebellum

Abstract: We examined the constitutive and inducible levels of microsomal cytochromes P450 1A1 and 1A2 (CYP1A) in rat cerebral cortex and cerebellum at the level of proteins by western blot analysis, and by catalytic activities via ethoxyresorufin O-deethylase (EROD) and methoxyresorufin O-demethylase (MROD). In the cerebral cortex, cytochrome P450 1A1 (CYP1A1) protein was more abundant than cytochrome P450 1A2 (CYP1A2) protein. Treatment with beta-naphthoflavone (beta-NF) caused a slight decrease in the level of the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 47 publications
(59 reference statements)
2
16
0
Order By: Relevance
“…This large increase in luciferase activity may in part be a result of basal luciferase activity that is nearly 100-fold higher than that observed in livers from untreated mice. Elevated levels of constitutive luciferase activity are in agreement with reports that Cyp1a1 is constitutively expressed in rodent brain (39,40). These results are also in agreement with previously published observations indicating that induced levels of Cyp1a1 accumulate in rat cerebral cortex and cerebellum (39).…”
Section: Characterization Of Hepatic Cyp1a1-luciferase Expression In supporting
confidence: 93%
See 1 more Smart Citation
“…This large increase in luciferase activity may in part be a result of basal luciferase activity that is nearly 100-fold higher than that observed in livers from untreated mice. Elevated levels of constitutive luciferase activity are in agreement with reports that Cyp1a1 is constitutively expressed in rodent brain (39,40). These results are also in agreement with previously published observations indicating that induced levels of Cyp1a1 accumulate in rat cerebral cortex and cerebellum (39).…”
Section: Characterization Of Hepatic Cyp1a1-luciferase Expression In supporting
confidence: 93%
“…Mouse Cyp1a1 is expressed constitutively and induced in adult brain (39,40), and we demonstrated that TCDD was capable of inducing CYP1A1-luciferase activity in adult brain from CYPLucR mice. In contrast, induction of CYP1A1-luciferase in brains from neonatal mice that were receiving TCDD through lactational exposure showed minimal induction.…”
Section: Discussionmentioning
confidence: 75%
“…CYP1A1 is expressed predominantly in extrahepatic tissue and abundantly in brain (McFayden et al, 1998;Iba et al, 2003). Our previous in vitro studies have suggested that heme deficiency leads to increased accumulation of CYP1A1 in the cytosol of COS-1 cells and untreated male mice .…”
Section: Discussionmentioning
confidence: 99%
“…However, heart and cerebral cortex displayed 30-to 50-and 60-to 1400-fold excesses of 6-HMEL, respectively. Uninduced rat cerebral cortex contains relatively little CYP1A2, but this can be induced considerably by ␤-naphthoflavone treatment (Iba et al, 2003). CYP1A2 is unlikely to be the source of the massively elevated MEL metabolite levels in the cerebral cortex.…”
Section: Michaelis-menten Parameters Estimated For Melatonin 6-hydroxmentioning
confidence: 96%
“…CYP1B1-mediated MEL 6-hydroxylation was then investigated in an organ that expresses CYP1B1, together with other CYP1 forms. Mouse brain was used because this organ was reported to express all three CYP1 forms (Granberg et al, 2003;Iba et al, 2003). In addition, whole brain homogenates were used for these studies in light of a report that CYP1B1 may be expressed in the nuclei of brain and other tissues (Muskhelishvili et al, 2001).…”
Section: Downloaded Frommentioning
confidence: 99%